Hierarchical comb brush architectures via sequential light‐mediated controlled radical polymerizations. Issue 15 (19th April 2016) - Narupai, Benjaporn; Poelma, Justin E.; Pester, Christian W.; McGrath, Alaina J.; Toumayan, Edward P.; Luo, Yingdong; Kramer, John W.; Clark, Paul G.; Ray, Paresh C.; Hawker, Craig J.
ABSTRACT: A novel strategy for the synthesis and characterization of branched polymer brushes by sequential light‐mediated controlled radical polymerizations is described. Initially, linear brushes are prepared by surface‐initiated copolymerization of methyl methacrylate and 2‐hydroxyethyl methacrylate (HEMA). In a subsequent step, the HEMA side chains are functionalized with initiating groups for secondary graft polymerization, leading to hierarchical, branched architectures. The increased steric bulk due to the polymer side chains results in a dramatic increase in film thickness when compared to the starting linear brushes. This strategy also allows chemical gradient and complex three‐dimensional structures to be obtained by employing grayscale photomasks in combination with controlled radical polymerization. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 2276–2284 Abstract : Comb‐type polymer brushes using light‐mediated controlled radical polymerization were developed. Linear copolymer brushes of methyl methacrylate and 2‐hydroxyethyl methacrylate (HEMA) were prepared, followed by functionalization of the HEMA groups with an initiator to generate secondary graft polymerization. Modulation of the light intensity using a grayscale photomask permits construction of complex and arbitrary three‐dimensional polymer brush nanostructures. This feature allows for independent control over the molecular weight of both the tethered linear and attached grafted chain.